Effects of a cognitive acceleration program in a low socio-economic high school in regional Australia - Oliver, Mary; Venville, Grady; Adey, Philip (Taylor & Francis Group, 2012)
This paper presents research on the effects of a cognitive acceleration intervention in science lessons on low socio-economic students in a government high school in regional Western Australia. Thinking Science Australia is a program currently being implemented in Australian junior high school classes. The research was conducted over two years as a case study in one school with students as they entered high school in Year 8 (n = 71). Findings show that significant cognitive gains were made, with concomitant improvement in the state-wide testing in science when participating students were in Year 9, aged 13 and 14. Teachers reported changes to the ways they teach and described the challenges in implementing the intervention program.